The Humanitarian Potential of Astronomy in Secondary Schools - As A Source of Humanization of Education in Teaching - Feruzakhon Olimjonovna , Dadaboeva (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the humanization of education as an important pedagogical problem. The state, content, and essence of humanization of the content of natural sciences in modern teaching are covered. The humanitarian potential of the subject of astronomy in general education schools is considered as a source of humanization of education in its teaching.